Event-Related Electrodermal Response to Stress: Results From a Realistic Driving Simulator Scenario. (February 2020) - Daviaux, Yannick; Bonhomme, Emilien; Ivers, Hans; de Sevin, Étienne; Micoulaud-Franchi, Jean-Arthur; Bioulac, Stéphanie; Morin, Charles M.; Philip, Pierre; Altena, Ellemarije
Objective: The study goal was to test whether induced stress during driving could be measured at the event level through electrodermal activity responses. Background: Stress measured in simulation scenarios could thus far show an overall change in the stress state, but not be well attributed to acute stressful events. Driving simulator scenarios that induce stress measurable at the event level in realistic situations are thus warranted. As such, acute stress reactions can be measured in the context of changing situational factors such as fatigue, substance abuse, or medical conditions. Method: Twelve healthy female participants drove the same route numerous times in a driving simulator, each time with different random traffic events occurring throughout. During one of the scenarios, unknown to the participants, 10 programmed neutral traffic events occurred, whereas in another scenario, at the same location, 10 stressful events occurred. Results: Electrodermal response results showed both effects of scenario type and of events. The amplitude of the electrodermal response was significantly correlated with subjective stress experience. Conclusion: We conclude that our developed ecological driving simulation scenarios can be used to induce and measure stress at the event level. Application: The developed simulator scenarios enable us to measure stress reactions in driving situations at the time when the event actually happens. With these scenarios, we can measure how situational factors, such as fatigue or substance abuse, can change immediate stress reactions when driving. We can further measure more specifically how induced driving stress can affect physical and mental functioning afterward.